Phyroseiid mites (Parasiriformes, Phytoseiidae) of Greece associated with different forest plants at different heights (Bollettino di zoologia agraria e bachicoltura, 2024)
A survey was carried out on phytoseiid mites associated with different forest plants. Euseius flnlandicus (Oudemans) was the most common species (40,1%), followed by Typhlodromus cryptus Athias-Henriot (27,3%), Typhlodromus cotoneastri Wainstein (27,3%) and Kampimodromus aberrans (Oudemans) (22,7%). E. finlandicus was found up to a height of m 1800 a.s.l., while K. aberrans up to m 2000 a.s.l. T. cryptus and T. cotoneastri were found between m 10 and m 850 a.s.l.
Keywords: census; Greece; Phytoseiidae; forest plants